Minimum size and positioning of imaging field for CBCT-scans of impacted lower third molars: a retrospective study - Ilo Anne-Mari; Ekholm Marja; Esmaeili Elmira Pakbaznejad; Waltimo-Siren Janna (BMC, 2022)
Background: Cone-beam Computed Tomography (CBCT) is widely used for preoperative 3D imaging of lower third molars. Hence, for this imaging indication, the present study aimed to define the minimum field-of-view (FOV) size and its optimum placement, to decrease radiation exposure, and highlight the need of computer-assisted FOV centering technique for dental CBCT devices. To facilitate proper placement of image field, lower second molar was chosen as reference.
Methods: The retrospective study included 50 CBCT-scans of 46 patients with mean age of 34 years. Based on the lower second molar, a three-dimensional coordinate was formed and the location of mandibular canal (MC) and the dimensions and locations of the lower third molars, and possible associated pathological findings were assessed. Accordingly, the FOV size and position for third-molar imaging were optimized, while ensuring encompassment of all relevant structures.
Results: The minimum cylindrical volume, covering lower third molars and MC, was 32.1 (diameter) × 31.6 (height) mm, placed in relation to the second molar crown, top 2.2 mm above cusp tips, anterior edge 6.7 mm in the front of the most distal point of the crown, and lingual edge 7.9 mm on the medial side of the lingual wall.
Conclusions: The optimized FOV for lower third molars was smaller than common standard small FOVs. We recommend using FOV volume 3.5∅ × 3.5 cm for third molars without associated pathology. Accurate FOV protocols are essential for development of new CBCT-devices with computer-assisted and indication-specific FOV placement.